2006
DOI: 10.1111/j.1600-0501.2006.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of material characteristics and/or surface topography on biofilm development

Abstract: Extrapolation of data from studies on different restorative materials seems to indicate that transmucosal implant surfaces with a higher surface roughness/surface free energy facilitate biofilm formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
949
5
67

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,118 publications
(1,101 citation statements)
references
References 125 publications
32
949
5
67
Order By: Relevance
“…Some authors have discussed the negative influence of supragingival roughness on biofilm formation and mechanical plaque control by the patient (2). A literature review (20) concluded that the defects on root surface are protected against the removal forces, increase the difficult in performing oral hygiene. This favors biofilm adherence, retention and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have discussed the negative influence of supragingival roughness on biofilm formation and mechanical plaque control by the patient (2). A literature review (20) concluded that the defects on root surface are protected against the removal forces, increase the difficult in performing oral hygiene. This favors biofilm adherence, retention and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that initial adhesion was promoted if both bacteria and the surfaces involved had similar hydrophobic properties 8,17,18) . In this study, the S. sanguinis cells suspended in saliva showed a hydrophilic nature.…”
Section: Discussionmentioning
confidence: 99%
“…The critical roughness threshold for plaque formation has been reported to be 0.2 µm (Teughels et al, 2006). A smooth surface adds to the patient's comfort, as already a surface roughness in the order of 0.3 mm can be detected by the tip of the patient's tongue (Jones et al, 2004).…”
Section: Introductionmentioning
confidence: 99%